Análise das estratégias utilizadas em educação à distância nas organizações brasileiras: estudo de caso em duas organizações de grande porte - Veloso, Carlos Augusto Barcellos (2007)
This essay studies both the learning process and professional improvement through continuing education within two companies: a national and a multinational one. It identifies the personnel management policy that both companies carry out. It also identifies the learning technological context which is being offered and contributes to continuing education comprehension used within corporative environment. It also presents thoughts and suggestions through experiences in case studies which were observed and analized